2015
DOI: 10.1189/jlb.4a1214-577rr
|View full text |Cite
|
Sign up to set email alerts
|

Superantigens produced by catheter-associated Staphylococcus aureus elicit systemic inflammatory disease in the absence of bacteremia

Abstract: SAgs, produced by Staphylococcus aureus, play a major role in the pathogenesis of invasive staphylococcal diseases by inducing potent activation of the immune system. However, the role of SAgs, produced by S. aureus, associated with indwelling devices or tissues, are not known. Given the prevalence of deviceassociated infection with toxigenic S. aureus in clinical settings and the potency of SAgs, we hypothesized that continuous exposure to SAgs produced by catheterassociated S. aureus could have systemic cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…, SEB in our model). In our experiment, as is evident from Figure 4 , the proportion of CD4 + and CD8 + T cells expressing TCR Vβ8 and Vβ6 was significantly different in the spleens of mice challenged with S. aureus SEB+ RN6734/pRN7114 compared to DR3 mice with wounds colonized with SEB− S. aureus RN6734/pRN7116, which was comparable to mice with uninfected wounds ( p < 0.001, p < 0.001; Figure 4 ) [ 17 , 18 ]. This observation combined with our finding that we were not able to culture any bacteria in blood, spleen or any tissue indicated that SEB produced in the skin was able to cause systemic immune activation.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…, SEB in our model). In our experiment, as is evident from Figure 4 , the proportion of CD4 + and CD8 + T cells expressing TCR Vβ8 and Vβ6 was significantly different in the spleens of mice challenged with S. aureus SEB+ RN6734/pRN7114 compared to DR3 mice with wounds colonized with SEB− S. aureus RN6734/pRN7116, which was comparable to mice with uninfected wounds ( p < 0.001, p < 0.001; Figure 4 ) [ 17 , 18 ]. This observation combined with our finding that we were not able to culture any bacteria in blood, spleen or any tissue indicated that SEB produced in the skin was able to cause systemic immune activation.…”
Section: Resultsmentioning
confidence: 51%
“…Histopathological evaluation of tissues from different mice groups showed the presence of inflammatory cell infiltrates in the livers, kidneys and lungs only in mice challenged with SEB+ S. aureus RN6734/pRN7114 compared to uninfected controls. Tissues from mice challenged with SEB− S. aureus RN6734/pRN7116 showed minimal or no inflammation ( Figure 5 ) [ 17 , 18 ]. The presence of these inflammatory changes only in mice challenged with SEB-producing S. aureus RN6734/pRN7114, but not its isogenic RN6734/pRN7116 strain not producing SEB, strongly suggests the involvement of SEB in eliciting this systemic inflammatory process.…”
Section: Resultsmentioning
confidence: 99%
“…The S. aureus strain IDRL-7420 [RN6734, containing a derivative with a large 3 0 deletion in SEB, pRN5543::seb(b.2) (pRN7116), referred to as SEB-SA], is an isogenic control for IDRL-7419 and does not produce any SAg including SEB. 54,64,65 RN6734 produces a-toxin and d-toxin. 66 We have shown previously that IDRL-7419 produces equivalent levels of SEB compared with clinical isolates 65 Only the SEBCSA, but not the SEB-SA, induces lethal pneumonia in HLA-DR3 transgenic at the inoculum tested, whereas C57Bl/B6 mice are not susceptible to lethal pneumonia.…”
Section: Induction Of Pneumoniamentioning
confidence: 99%
“…54,64,65 RN6734 produces a-toxin and d-toxin. 66 We have shown previously that IDRL-7419 produces equivalent levels of SEB compared with clinical isolates 65 Only the SEBCSA, but not the SEB-SA, induces lethal pneumonia in HLA-DR3 transgenic at the inoculum tested, whereas C57Bl/B6 mice are not susceptible to lethal pneumonia. 54 Experimental pneumonia was induced following our previously published protocol.…”
Section: Induction Of Pneumoniamentioning
confidence: 99%
“…This is termed as systemic inflammatory response syndrome and generally culminates in multiple organ dysfunction syndrome, which can be lethal (8). However, in certain clinical situations, chronic exposure to small amounts of SSAg can occur e.g., chronic S. aureus carriers, chronic or recurrent staphylococcal skin and soft tissue infections or catheter-associated biofilm infection (9, 10). The immunopathology ensuing from chronic immune activation mediated by SSAg could be distinct from that resulting from acute exposures.…”
Section: Introductionmentioning
confidence: 99%